2020
DOI: 10.1111/1365-2664.13595
|View full text |Cite
|
Sign up to set email alerts
|

Ecological impacts of pesticide seed treatments on arthropod communities in a grain crop rotation

Abstract: 1. While many studies have investigated non-target impacts of neonicotinoid seed treatments (NSTs), they usually take place within a single crop and focus on specific pest or beneficial arthropod taxa.2. We compared the impacts of three seed treatments to an untreated control: imidacloprid + fungicide products, thiamethoxam + fungicide products and fungicide products alone in a 3-year crop rotation of full-season soybean, winter wheat, doublecropped soybean and maize. Specifically, we quantified neonicotinoid … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 63 publications
(114 reference statements)
1
14
0
Order By: Relevance
“…Therefore, pesticide risk to all soil invertebrates in the United States is essentially estimated by harm to a species that generally does not come into contact with the soil and does not share any of the same exposure pathways. For example, most neonicotinoid seed coatings end up in the soil, and concentrations of neonicotinoids can be drastically higher in soil than in pollen (Goulson, 2015;Willis Chan et al, 2019;Dubey et al, 2020;Main et al, 2020).…”
Section: Surrogacy In Pesticide Regulationmentioning
confidence: 99%
“…Therefore, pesticide risk to all soil invertebrates in the United States is essentially estimated by harm to a species that generally does not come into contact with the soil and does not share any of the same exposure pathways. For example, most neonicotinoid seed coatings end up in the soil, and concentrations of neonicotinoids can be drastically higher in soil than in pollen (Goulson, 2015;Willis Chan et al, 2019;Dubey et al, 2020;Main et al, 2020).…”
Section: Surrogacy In Pesticide Regulationmentioning
confidence: 99%
“…Unlike some transgenic crops (i.e., Bt hybrids), NSTs were not developed in response to new or recurring pest outbreaks; in fact, pest populations remain at historic lows in many US crops ( 4 , 5 ). As a result, studies have struggled to document a clear agronomic or economic benefit from using NSTs in the United States and Canada ( 6 13 ), likely due to the sporadic occurrence of the pests they are purported to control. In a recent analysis, <5% of corn fields in Quebec experienced a measurable benefit from the use of NSTs ( 14 ).…”
mentioning
confidence: 99%
“…Although a significantly lower amount of active ingredient is applied per unit area when sowing treated seeds [15,27] than when applying granulated insecticides, the treated area is significantly larger due to the prophylactic application. There is a growing body of research showing that sowing treated seeds consequently has a negative impact on beneficial entomofauna [35,49,50]. Research by Dubey et al [50] showed that seed treatments with neonicotinoids can affect arthropod communities, including important natural enemies, even when environmental persistence and active ingredient concentrations are low.…”
Section: Insecticides For Seed Treatmentmentioning
confidence: 99%